Highly Cited in the South: International Collaboration and Research Recognition Among Brazil's Highly Cited Researchers. (February 2020) - Martinez, Magdalena; Sá, Creso
For researchers in the global South, international recognition in science arguably involves engaging with the norms, ideas, and people leading research activity in the global North. This article explores the relationship between international research collaboration and the publication activity of highly cited researchers in Brazil, a country that exerts regional leadership in scientific production in Latin America, but remains relatively peripheral to global science. This study examined the career trajectories and publication patterns of highly cited researchers based in Brazilian universities, using Web of Science and CV data. Our findings show a pattern of international mobility among the Brazilian highly cited researchers from the early stages of their careers. With few exceptions, engagement with the academic Anglosphere is central to their achievement of highly cited status, which is derived from co-authored publications with collaborators from the United States, the United Kingdom, and Australia in large teams.